The Role of Brain/Behavioral Systems and Emotional Processing in Predicting Social Anxiety of Students - Majid Zargham Hajebi; Saeed Pourabdol; Mahdi Beyki; Seyed Hamed Sajjadpour (Shiraz University of Medical Sciences, 2019)
Background: Social anxiety disorders are among disorders that decrease the academic performance of students and cause emotional and behavioral problems. Objectives: The aim of this study was to evaluate the role of brain/behavioral systems and emotional processing in predicting social anxiety of students. Methods: This research was descriptive and correlational. The research population included all 5th grade male students of Ardabil city during years 2016 to 2017, among which 123 students were selected by the multi-stage cluster sampling method. Data collection was done through brain/behavioral systems scale, emotional processing, and social anxiety questionnaire. For data analysis, the researchers used Pearson's correlation and multiple regression analysis. Results: The results showed mean (and standard deviation) of BAS, BIS, and FFS for emotional processing and social anxiety among students under study was 77.26 (2.76), 79.78 (57), 82.93 (3.25), 114.21 (22.84), and 32.41 (14.22), respectively. Also, the results showed that there was a significant negative correlation between behavioral activation system (BAS) and students' social anxiety (P < 0.001). Also, a significant positive relationship was found between behavioral inhibition system and fight-or-flight system with students social anxiety (P < 0.001). In addition, there was a negative correlation between social anxiety and emotional processing. Results of regression analysis showed that 46% of the variance in social anxiety of students was significantly explained by brain/behavioral systems and emotional processing variables. Conclusions: Based on these results, it could be said that the relationship between individual differences, emotional processes, and brain behavioral processes can be an important factor in dealing with anxiety.